The Policy of Village Web-Based Land Affairs Administration Management as Prior Evidence in Land Registration in Indonesia - Rina Yulianti; Mufarrijul Ikhwan (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract Indonesia has not had good land affairs administration management yet at Village Government Level. Land conflict or dispute derives from village’s very limited, manual, and outdated data. Data at village level still refers to data inherited from East Indie government time. The data available cannot meet the modern need today. Relatively inadequate human resource at village level and low awareness of land affair administration discipline within society make the change of prior data supply difficult. This research will study the utilization of village web in providing prior evidence of land registration and the juridical construction of web-based land affairs administration management to the organization of village government. The normative juridical research method with statute and conceptual approaches was used to address the problem of research. The result of research showed that the data of land affairs presented by village web can be the prior evidence as governed in Government Regulation about Land Registration and the provision without changing the source of evidence that can be either written evidence or testimony. The juridical construction of village web-based land affairs administration management derived from Village Law, Archive Law, and Information and Electronic Transaction Law. Village government can present the web-based land affairs data and make it electronic evidence.Keywords: Management, Administration, Land Affairs, Village Web Desa. Konflik maupun sengketa tanah bersumber dari data desa yang masih sangat minim, serba manual dan usang. Data-data ditingkat desa masih mengacu pada data peninggalan sejak jaman pemerintah Hindia Belanda. Data yang tersedia tidak mampu lagi mengikuti kebutuhan modern saat ini. Sumber daya manusia yang relative kurang ditingkat desa serta kesadaran masyarakat terhadap tertib administrasi pertanahan yang rendah menyulitkan berubahnya penyediaan data awal. Penelitian ini akan mengkaji pemanfaatan web desa dalam menyediakan bukti awal pendaftaran tanah dan konstruksi yuridis tata kelola administrasi pertanahan berbasis web bagi penyelenggaraan pemerintah desa. Metode penelitian yuridis normatif dengan pendekatan perundang-undangan dan pendekatan konseptual digunakan untuk menjawab persoalan penelitian. Hasil penelitian menunjukkan bahwa data-data pertanahan yang disajikan oleh web desa dapat menjadi bukti awal sebagaimana diatur oleh Peraturan Pemerintah tentang Pendaftaran Tanah dengan ketentuan tanpa merubah sumber alat bukti yang dapat berupa bukti tertulis maupun kesaksian. Konstruksi yuridis tata kelola administrasi pertanahan berbasis web desa bersumber dari UU Desa, UU Arsip dan UU Informasi Transaksi Elektronik. Pemerintah Desa dapat menyajikan data pertanahan berbasis web dan dijadikan sebagai alat bukti elektronik.Kata Kunci: Tata Kelola, Administrasi, Pertanahan, Web Desa АннотацияИндонезия всё еще не имеет надлежащее управление земельной администрации на уровне деревенских властей. Конфликты и земельные споры происходят из деревенских данных, которые все еще очень минимальны, полностью ручные и устаревшие. Данные на уровне деревень по-прежнему относятся к устаревшим данным со времен правительства Голландской Ост-Индии. Доступные данные больше не могут соответствовать сегодняшним потребностям. Относительная нехватка человеческих ресурсов на уровне деревень и низкий уровень осведомленности общественности о порядке управления земельной администрации затрудняли изменение предоставления исходных данных. В этом исследовании будут рассматриваться использование деревенского веба для предоставления первоначального свидетельства регистрации земли и юридическое оформление управления земельной администрации на базе веб-версии для организации деревенского правительства. Для решения исследовательских задач используются нормативные юридические методы исследования с нормативным и концептуальным подходом. Результаты исследования показывают, что земельные данные, представленные на деревенском вебе, могут быть первоначальным доказательством в соответствии с Постановлением Правительства о Регистрации Земли, при условии, что не измененился источник доказательств, которые могут быть в форме письменных доказательств или свидетельских показаний. Юридическое построение управления земельной администрации на базе деревенской веб-версии исходит из Закона о деревнях, Закона об архивах и Закона об информации электронных транзакций. Правительство деревни может предоставлять данные о земле на базе веб-версии и служить в качестве электронного доказательства.Ключевые Слова: Управление, Администрация, Земля, Деревенский Веб